Talvinen tarina - Shakespeare, William, 1564-1616; Cajander, Paavo Emil, 1846-1913 (Salt Lake City, UT : Project Gutenberg, 2014)
"Talvinen tarina" by William Shakespeare is a play originally published in 1623. A king's jealous rage destroys his family when he falsely accuses his pregnant wife of betrayal and abandons their newborn daughter. Years of grief follow his devastating mistake. Sixteen years later, the lost daughter$1 (Braised by shepherds$1 (Bfalls in love with a prince, setting in motion events that may bring reconciliation and healing to the broken families, though the damage seems irreversible. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Winter%27s_Tale Wikipedia page about this book: https://fi.wikipedia.org/wiki/Talvinen_tarina
Release date is 2014-02-08
Produced by Tapio Riikonen
Keywords: Fathers and daughters -- Drama; Married people -- Drama; Tragicomedy; Castaways -- Drama; Sicily (Italy) -- Kings and rulers -- Drama